Assessment of Pulmonary Changes in Patients with Ankylosing Spondylitis with High Resolution Computed Tomography - Ersin Öztürk; Ümit Dinçer; Onur Sıldıroğlu; Engin Çakar; Güner Sönmez; Hakan Mutlu; Mehmet Zeki Kıralp; Çınar Başhekim; Hasan Dursun; Eşref Kızılkaya (Archives of Rheumatology, 2008)
Objective: In this study, our aim was to investigate the pleural and parenchymal changes and their frequency in patients with ankylosing spondylitis using high resolution computed tomography. Patients and Methods: A total of 23 patients with the diagnosis of ankylosing spondylitis were included in the study. In all patients high resolution computed tomography of the lung was performed after maximum inspiration and expiration. Previous pulmonary findings of 11 cases were used for the analysis of the images. Results: Pulmonary changes were detected in 13 (57%) of 23 patients using high resolution computed tomography. No parenchymal changes were detected in the remaining 10 patients. The most frequently detected finding was parenchymal nodules seen in 11 (48%) patients. This was followed by parenchymal band formation in 9 (39%) patients. In addition, mosaic pattern in 6 (26%) patients, bronchiectasis in 5 (22%) patients, emphysema, interlobular septal thickening, pleural thickening and/or ground glass opacity in 3 (13%) patients, bronchial wall thickening in 2 (9%) patients and honeycomb lung in 1 (4%) patient, were detected. Conclusion: High resolution computed tomography of the lung is an effective method in demonstrating the pulmonary changes in patients with ankylosing spondylitis. (Rheumatism 2008; 23: 38-41)